A novel power stability drive system of semiconductor Laser Diode for high-precision measurement. (June 2019) - Huang, He; Ni, Jingxue; Wang, Huifeng; Zhang, Jiajia; Gao, Rong; Guan, Limin; Wang, Guiping
In view of the strict requirements of the current high-precision measurement system for stable output power of the semiconductor LD (Laser Diode), a semiconductor LD stable power drive and multi-closed-loop control system are proposed after analyzing the semiconductor laser's P–I (Power–Current) characteristics and temperature characteristics. The system uses a microcontroller as the core control unit and realizes the stable power output control of the semiconductor laser by controlling the current, power and temperature parameters. In this system, first, the control structure model of the controlled object has been designed. Second, a controllable closed-loop constant current feedback drive circuit has been designed and a high-precision controllable constant current drive circuit of the semiconductor laser has been obtained. Furthermore, the control circuit has been designed based on the neural PI (Proportional-Integral) control model and realizes the short-term stable power output of the semiconductor LD. Finally, a closed-loop temperature control system is designed to ensure that the operating temperature of the semiconductor laser is relatively stable and a long-term stable power output is obtained. By designing the hardware and software of the control system and conducting long-term experiments in the laboratory, we found that the system can guarantee the output power within 1 W of PD (Proportional-Differential) LD, and its long-term power stability can reach 1%. This system has a certain reference significance in using semiconductor lasers for high-quality detection when there are stringent requirements for power.